Zn doped MAPbBr3 single crystal with advanced structural and optical stability achieved by strain compensation. Issue 6 (5th February 2020) - Li, Ruxue; Chen, Shaoqing; Li, Xia; Yin, Guoxin; Gong, Youpin; Yu, Jiahao; Pang, Guotao; Liu, Jianxun; Liu, Yanjun; Ni, Zhenhua; Zhang, Liyuan; Chen, Rui; et al.
Abstract : Strain compensation in a Zn doped MAPbBr3 single crystal under light illumination gives rise to improved photostability in terms of temperature and time to the benefit of photodetector. Abstract : A mechanistic understanding of perovskite degradation is one of the most urgent issues to push perovskite devices toward commercial applications. Surface coverings will lower the electrical injection and light extraction efficiency of perovskites. Therefore, structural modification of Zn doped perovskites has been proposed herein. The Zn doping will induce local lattice strain due to smaller ionic radius. It is interesting that the lattice structure at atomic resolution has been observed directly through cryo-TEM. Under light illumination, the photostriction will compensate for the local lattice strain, which leads to structural stability as evidence suggests no phase transition in temperature ranges of the temperature-dependent photoluminescence spectra. In addition, MPZB also shows less than 3% decrease in PL intensity after 60 days. This is because the Zn doping induced the lowest defect density in the MPZB SC (density of trap-states n trp = 6.33 × 10 8 cm −3 ), which has been confirmed by the high performance of the photodetector. Such strain compensation is expected to fundamentally improve the stability of photoelectric devices.